Green Transformational Leadership (GTL) and its Impact on Employees' Green Behaviors Through the Mediating Role of Social Responsibility Field Study in the Basra Implementation Directorate - Layla Laftah Ali; Amal Farhan Swadi (International Journal of Economics, Management and Accounting, 2025)
The study seeks to assess the influence of green transformational leadership, an innovative method for shaping employees' environmentally friendly behaviors, via the mediating role of social responsibility. The research was carried out at the Basra Implementation Directorate, where a sample of 30 personnel from several areas within the directorate was chosen. Data was gathered by a questionnaire including a series of inquiries pertaining to the specified variables. Statistical testing techniques and the SPSS program were employed to assess the validity of the data by analyzing the correlations among various variables.  The research was based on a primary hypothesis asserting a substantial direct and indirect influence of GTL on employees' environmentally friendly activities. The study yielded various findings, indicating that GTL influences employees' environmentally friendly activities and validated the mediation function of social responsibility.